Asian environmental documentaries - Deocampo, Nick (Center for New Cinema, 2012)
Documentaries on how local communities develop indigenous ways to respond to environmental challenges. Two stand out as notable responses, spirituality and community action. These documentaries are products of three years of research and production in Kali Code (Indonesia), Khiriwong (Thailand) Tasik Chini (Malaysia), Batanes (Phillipines) and Biwako (Japan).